Kaempferia parviflora extract increases energy consumption through activation of BAT in mice. Issue 6 (15th July 2014) - Yoshino, Susumu; Kim, Minji; Awa, Riyo; Kuwahara, Hiroshige; Kano, Yuriko; Kawada, Teruo
Abstract Kaempferia parviflora (KP) is a member of the ginger family and is known in Thailand as Thai ginseng, Krachai Dam or Black Ginger. The K. parviflora extract (KPE) was previously reported to have a number of physiological effects; however, the antiobesity effects of KPE and its mechanisms remain to be elucidated. In this study, we conducted KPE feeding experiments (low dose: 0.5% KPE, high dose: 1.0% KPE) in mice to examine the antiobesity effects. For both 0.5% KPE and 1.0% KPE, 7 weeks' feeding of KPE contained in a high‐fat diet (HFD) significantly decreased body weight gain, intraabdominal fat accumulation, and plasma triglyceride and leptin levels. Concurrently, KPE administration increased oxygen consumption in mice fed on a HFD. We also found that 1.0% KPE feeding significantly increased the uncoupling protein 1 (UCP1) expression in brown adipose tissue (BAT). Moreover, KPE administration increased urinary noradrenaline secretion levels. These results demonstrate that KPE promotes energy metabolism by activation of BAT, at both doses and up‐regulation of UCP1 protein at a high dose. Although numerous challenges remain, the present study demonstrated that KPE suppresses HFD‐induced obesity through increased energy metabolism.